Computer-Assisted Surgery Patterns of Ligamentous Deformity of the Knee: A Clinical and Cadaveric Study - Schwarzkopf, Ran; Hadley, Scott; Abbasi, Mohammed; Meere, Patrick A. (The Journal of Knee Surgery, 2013)
Knee malalignment during total knee arthroplasty (TKA) is commonly classified as either varus or valgus on the basis of a standing anteroposterior radiograph. Computer-assisted surgery (CAS) navigation TKA provides precise dynamic evaluation of knee alignment throughout the full range of motion (FROM). The goal of this study was to classify patterns of CAS-generated knee deformity curves that match specific soft tissue contracture combinations. This can then be applied as an algorithm for soft tissue balancing on the basis of the preoperative knee deformity curve. Computer navigation–generated graphs from 65 consecutive TKA procedures performed by a single surgeon were analyzed. A stress–strain curve of the coronal alignment of the knee was recorded throughout FROM before bony resection. All graphs were classified into groups according to their pattern. Cadaveric knee models were then used to test the correlation between isolated and combined ligamentous contractures and identified CAS deformity curves. An analysis of the intraoperative knee alignment graphs revealed four distinct patterns of coronal deformity on the basis of intraoperative data: 13% diagonal, 18.5% C-shaped, 43.5% comma shaped, and 25% S-shaped. Each represents the change in varus and valgus alignment during FROM. All patterns were reproduced with cadaveric knees by recreating specific contracture constellations. A tight posterior capsule gave an S-shaped curve, a tight lateral collateral ligament gave a C-shaped curve, tight medial collateral ligament gave a diagonal curve, and a tight posterior lateral corner gave a comma-shaped curve. Release of the specific contractures resulted in correction of all patterns of deformity as measured by CAS. We propose a new classification system for coronal plane knee deformity throughout FROM. This system intends to match individual and combined soft tissue pathological contractures to specific stress–strain curves obtained through routine knee CAS preparation. This classification system may provide surgeons with a general guide for soft tissue balancing during computer-navigated TKA.
Keywords: computer-assisted surgery; total knee arthroplasty; ligament deformity; knee balancing